Narrating stories of change: women recounts how STIBs implementation has changed their lives in WB learning labs - Puskur, Ranjitha; Gartaula, Hom Nath; Mukhopadhyay, Prama; Chadha, Deepali (CGIAR Initiative on Gender Equality, 2024)
Caption: This video highlights the transformative impact of the CGIAR Initiative on Gender Equality through the voices and narratives of two women farmers from the learning labs in West Bengal, India. It demonstrates how the context-specific socio-technical innovation bundles, designed and implemented as part of the EMPOWER Work Package, have increased women’s agency, enhanced their resilience to climate change and strengthened their role in the agri-food system. Through their personal stories, the video illustrates the tangible benefits of these innovations. Their journey emphasizes the crucial role of gender-inclusive solutions in building sustainable and climate-resilient agricultural communities.